Religiosity Aspect in Consumer Behaviour: Determinants of Halal Meat Consumption - Jusmaliani, Jusmaliani; Nasution, Hanny (UI Scholars Hub, 2021)
Previous studies indicate that religion may influence consumer attitude and behavior in general, especially in food purchasing decisions and eating habits. There are limited studies that examined the role of religiosity in consumer behaviour; especially in relations to halal meat consumption. Due to gaps found in the literature, this study investigates the determinants of intention to eat halal meat. It also examines the levels of determinants of halal meat consumption between Indonesian Muslim living in Jakarta and Melbourne. Respondents were personally and electronically contacted. In total, 160 questionnaires were completed for this initial study. The results indicate that behavioural control and availability of halal meat have significant impact on intention to eat halal meat. The results further suggest that in general there are no significant differences in the levels of determinants of halal meat consumption between Indonesian Muslim living in Jakarta compared to those of in Melbourne, except for availability of halal meat. This study contributes to the marketing literature focuses on the impacts of religion on consumer behaviour which is still under researched.